The impact of youtube video as a media to improve students’ listening comprehension in sultan ageng tirtayasa university english department 2019 class a - Syafrizal, Syafrizal; Wijaya , Michael (LPPM Universitas Mercu Buana Yogyakarta, 2023)
Based on the problems that had been found by the author, this research are intended to find out and understand about the impact of using YouTube video to improve students’ listening comprehension in Sultan Ageng Tirtayasa University English Department 2019 Class A and their perception toward the implementation of YouTube video to improve their listening comprehension. This research used a qualitative approach and to obtain primary data is used an questionnaire, and also to obtain secondary data is used literature study. Based on the findings, YouTube video had a lot of positives impact to improve their listening comprehension and effective to be implemented as media to improve their listening comprehension